2014
DOI: 10.1378/chest.13-2708
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fibroproliferation by Chest High-Resolution CT Scan in Resolving ARDS

Abstract: BACKGROUND:In ARDS, the extent of fibroproliferative activity on chest high-resolution CT (HRCT) scan has been reported to correlate with poorer short-term outcomes and pulmonaryassociated quality of life. However, clinical factors associated with HRCT scan fi broproliferation are incompletely characterized. We questioned if lung compliance assessed at the bedside would be associated with fi broproliferation on HRCT scans obtained during the resolution phase of ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…The imbalance between MMPs and TIMPs favors fibrosis, and this imbalance has been reported in the lungs of patients with ARDS and in animal models (11, 12, 33, 34). Compared with the control, lung of LPS‐treated mice showed increased collagen fiber content in the alveolar septa (P < 0.01; Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The imbalance between MMPs and TIMPs favors fibrosis, and this imbalance has been reported in the lungs of patients with ARDS and in animal models (11, 12, 33, 34). Compared with the control, lung of LPS‐treated mice showed increased collagen fiber content in the alveolar septa (P < 0.01; Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Collagen deposition has been observed in the lungs of patients with ARDS and in animal models (11, 12, 33, 34, 52), and this change has been suggested to be caused by alterations in ECM components (11, 12). In animal models, it has been shown that 24 h after LPS instillation, the deposition of some ECM components is increased (52, 53).…”
Section: Discussionmentioning
confidence: 99%
“…The group with well-aerated lung region/pTLC ≥40 % showed better survival outcome. Some reports have noted that patients with large ill-aerated lung regions experience poorer prognosis than patients with small ill-aerated lung regions [4][5][6]16], but no reports have focused on the well-aerated lung region of patients with ARDS. This is the first report to describe the relationship between well-aerated lung region and prognosis in patients with ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…2 Whereas a conventional chest x-ray is mandatory for the diagnosis of ARDS, computed tomography (CT) is not required to satisfy the diagnostic criteria outlined in the Berlin definition. However, CT scans in patients with ARDS are often performed for the following indications: confirmation of diagnosis, 3 assessment of recruitability, 4 identification of a pulmonary or extrapulmonary cause, 5 prediction of prognosis, [6][7][8] and follow-up. 9 Many ARDS centers, including our department, routinely perform CT scans in patients with ARDS, believing that this may yield clinically relevant information.…”
Section: Introductionmentioning
confidence: 99%